TALENT MANAGEMENT PRACTICES, INCLUSIVE LEADERSHIP, AND EMPOWERMENT CLIMATE AS DETERMINANT OF EMPLOYEE ENGAGEMENT OF STATE-OWNED ENTERPRISES (SOEs) - Emi Wakhyuni; Trisnia Manggiasih; Pungky Eka Ratnasari; Hillary O. Odor; Oluwabusayo Olanrewaju Oni (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
Abstract This research is motivated by the low level of employee engagement in State-Owned Enterprises (BUMN), which are often faced with bureaucratic rigidity and limitations in human resource management, while empirical studies that integrate talent management, inclusive leadership, and empowerment climate practices remain relatively limited. This study aims to comprehensively analyze the direct and simultaneous influence of these three variables on employee engagement. A quantitative approach was used, involving 160 BUMN employee respondents, and the data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The research results show that talent management practices have a positive, significant effect on employee engagement by increasing competency development and talent retention, while inclusive leadership strengthens engagement by fostering an open, fair, and supportive work environment. In addition, the empowerment climate has been shown to act as a reinforcing mechanism, deepening the influence of these two variables on employee engagement. These findings make theoretical contributions by expanding the conceptual framework of employee engagement through the integration of inclusive leadership perspectives and an empowering climate, and practical contributions for BUMN managers in designing adaptive talent management strategies, inclusive leadership, and an empowering work environment to improve organizational performance sustainably.